Customer acceptance towards the marketing mix at Lazaria shop Ayer Keroh fly-over restaurant Melaka / Shahiela Akma Abdul Azis - Abdul Azis, Shahiela Akma (Faculty of Business and Management, 2005)
In today's market competition, retailers have to evaluate the performance in order to compete with the competitors. Therefore, researcher has made a discussion with supervisor to come out with several factors that influence the customer acceptance towards Lazaria Shop. The important factors are the four elements in the marketing mix: product, price, place and promotion. The main purpose of this study is to get as much possible information in order to help the organization to plan better for the success in the future and also enhance customers' satisfaction. Since the company will target more sales and profit in the future, all the information are important to be recognized in order to increase the performance and to face intense competition from the competitors. Lazaria Shop also has to identify the weaknesses from the existing business and try to make improvement in future to attract more customers visit the shop and not to make the same mistakes as before.